Sealable Peelable Polyester Film
The cap liner film with a polyester base and tailored Copoliester layers addresses inconsistent heat seal adhesion in conventional liners, ensuring stable seals and improved quality control through controlled temperature fluctuations and aging resistance.
Patent Information
- Application Number
- JP2024515514
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-09
- Filing Date
- 2022-09-09
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2042-09-09
AI Technical Summary
Conventional cap liners experience inconsistent heat seal adhesion strength due to uneven temperature profiles during induced heating, leading to issues like partial seals, residue after peeling, and increased adhesion strength over time, complicating quality control.
A cap liner film composed of a polyester base layer and a heat-sealable polymer layer, incorporating Copoliester A and B with specific glass transition temperature differences, ensures consistent adhesion strength by minimizing fluctuations due to temperature changes and aging.
The film provides stable and consistent heat seal adhesion, reducing leakage risks and residue, while simplifying quality control processes by maintaining seal integrity over time.
Smart Images

Figure 0007626904000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a sealable, peelable film comprising a polyester substrate coated with a copolyester composition, and the use of such a film in packaging, particularly as a cap liner film. The film of the present invention exhibits improved seal and peel properties. [Background technology]
[0002] Heat-sealable peelable films have long been used in food and beverage packaging to seal and keep items fresh in the container before final use by the consumer. Typically, heat-sealable peelable films are multi-layer films, with a substrate layer providing the necessary strength and one or more additional layer(s) providing the heat-sealable functionality. Examples of such sealant composite films include those that include a substrate layer of polyester (typically polyethylene terephthalate (PET)) onto which a heat-sealable layer is extrusion coated. Such sealant films should form a strong heat-seal bond to the container to avoid leakage of the package contents and preserve their freshness, but not so strong that the film cracks during peeling. An advantageous feature of sealant films is that they should exhibit a "clean peel", i.e., no residue of the heat-seal layer or cap liner should remain on the container after peeling.
[0003] One such packaging application for sealant films is as a cap liner. A cap liner is a device that is sealed onto the top of a container, such as a bottle, to preserve and secure the contents of the container and avoid leakage. Cap liners provide a tamper-evident hermetic seal suitable for use with foods, drugs, beverages, alkalis, acids, oils, organic solvents, flammable materials, powders, pellets, and many other products. They are particularly effective for products that must avoid contamination, oxidation, and moisture. Prior to sealing the container, cap liners are usually inserted into an appropriate cap or closure device, typically by the cap manufacturer.
[0004] Cap liners can be one-piece or two-piece, depending on the identity and intended use of the product. One-piece liners are typically foam-backed or paper-backed laminates that are essentially composed of a paper or foam layer, an adhesive layer, a metal foil layer, and a heat-sealable film, in that order. Two-piece liners are typically multi-layer laminates that include a pulp board layer, a wax layer, a metal foil layer, and a heat-sealable film, in that order. The heat-sealable film in such cap liners typically consists of a polymer substrate layer and a heat-sealable polymer layer, and such multi-layer film is disposed in the cap liner such that the polymer substrate layer is adjacent to the metal foil layer. Such cap liners are typically manufactured by first producing a multi-layer film that includes a polymer substrate layer and a heat-sealable polymer layer, typically by coextrusion of the two layers, or by coating a heat-sealable polymer onto a preformed polymer substrate. The multi-layer film is then laminated with metal foil and other layers to provide the cap liner.
[0005] When sealing a container with a cap including a cap liner, the product is filled into the container, the cap is placed in place, and then the filled container cap is exposed to heat, and the heat-sealable polymer layer of the cap liner inside the cap adheres to the rim of the container. In a one-piece cap liner, the entire liner is peeled off from the cap after the heat-sealing process. In a two-piece cap liner, the heating process melts the wax, which is then absorbed into the pulp board and peeled off from the foil layer, leaving the pulp board layer inside the cap to improve resealing after the foil liner is removed. Thus, in use, the cap liner (or, in the case of a two-piece liner, the multi-layer portion thereof that remains sealed to the container) is peeled off from the container to access the contents stored inside the container. One-piece cap liners are typically used for disposable or dry products, while two-piece cap liners are typically used when there is liquid in the container or when the container is to be resealed. The two-piece liner allows the package to function as a resealable multi-serving container. Optionally, the top surface of the cap liner, which is sealed to the container and visible after the cap is removed, may have consumer information printed on it.
[0006] The heating step used to seal the cap liner to the container is typically accomplished by induction heating. An induction coil in the sealing head creates a magnetic field that generates heat in the metal foil layer, which is transferred to the heat-sealable polymer layer, thereby creating a heat seal bond between the heat-sealable polymer layer and the container. The induction heating step typically produces a seal temperature in the range of about 120 to about 205°C.
[0007] One problem with conventional cap liners currently on the market is that the strength of the heat seal bond can vary greatly with the sealing temperature. In particular, the bond strength increases with increasing sealing temperature. This is problematic because the magnetic field in conventional induction heating systems creates a non-uniform temperature profile across the cap liner, which results in heat seal bonds with different bond strengths in different areas around the edge of the container, i.e., the heat seal bond within a single cap liner is not consistent. These defects in the cap liner heat seal bond are called "partial seals" or "overheated seals" and can cause one or more of the following disadvantages: (i) leakage of liquid contents; (ii) reduced shelf life of contents; (iii) residue remaining on the edge of the container after peeling (i.e., not a clean peel); and (iv) scorching / browning of the container or foil.
[0008] An additional problem with conventional cap liners is that the strength of the heat seal bond can increase significantly over time, a process known as "sealed sample aging." This complicates the process of optimizing the sealing conditions in the induction heating system and makes downstream product quality control difficult. Summary of the Invention
[0009] It is an object of the present invention to address one or more of the problems set forth above. In particular, it is an object of the present invention to provide a cap liner that minimizes variation in heat seal bond strength with variations in sealing temperature and / or minimizes increase in heat seal bond strength over time.
[0010] According to a first aspect of the present invention, there is provided a polymeric film comprising a polyester substrate layer and a heat-sealable polymer layer disposed on one surface of the polyester substrate layer, wherein the heat-sealable polymer layer is selected from the group consisting of W A A copolyester A having a glass transition temperature Tg(A) in an amount of W B and a copolyester B having a glass transition temperature Tg(B) in an amount of (i) W A >W B , (ii) W A is at least 50% by weight of the total weight of the heat-sealable polymer layer; (iii) W B is at least 10% by weight of the total weight of the heat-sealable polymer layer; (iv) Tg(A)>Tg(B); (v) Tg(B) is in the range of -35°C to -10°C, and (vi) Tg(A) is preferably in the range of -15°C to 5°C.
[0011] The polyester substrate layer is a self-supporting film or sheet, which means a film or sheet that can exist independently in the absence of a supporting substrate.
[0012] The polyester substrate layer is preferably an oriented film, preferably uniaxially or biaxially oriented, preferably biaxially oriented film.
[0013] The substrate layer may be described as semi-crystalline. As used herein, the term "semi-crystalline" refers to a film exhibiting a crystallinity of at least 5%, preferably at least 10%, preferably at least 15%, preferably at least 20%, preferably at least 25%, typically no more than 50%, or no more than 45%, or no more than 40%.
[0014] The polyester of the substrate layer is preferably a crystallizable thermoplastic polyester. Synthetic linear polyesters are preferred. Suitable polyesters include terephthalic acid, isophthalic acid, phthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid or 2,7-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, hexahydro-terephthalic acid, 1,10-decanedicarboxylic acid, and polyesters of the general formula C n H 2n(COOH)2 (wherein n is 2 to 8), such as aliphatic dicarboxylic acids including succinic acid, glutaric acid, sebacic acid, adipic acid, azelaic acid, suberic acid, or pimelic acid; and one or more glycols, particularly aliphatic or alicyclic glycols, such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, and 1,4-cyclohexanedimethanol (CHDM).
[0015] The dicarboxylic acid component of the substrate layer polyester preferably comprises at least one aromatic dicarboxylic acid (preferably selected from terephthalic acid and 2,6-naphthalenedicarboxylic acid, preferably terephthalic acid), and optionally further comprises a second different dicarboxylic acid, preferably selected from the dicarboxylic acids mentioned above, preferably from aromatic dicarboxylic acids (particularly isophthalic acid) and aliphatic dicarboxylic acids mentioned above. Thus, the polyester is preferably derived from an aromatic dicarboxylic acid, preferably terephthalic acid or 2,6-naphthalenedicarboxylic acid, preferably terephthalic acid. Preferably, the dicarboxylic acid component of the substrate layer polyester contains only one aromatic dicarboxylic acid, which is preferably terephthalic acid or 2,6-naphthalenedicarboxylic acid, preferably terephthalic acid.
[0016] The glycol component of the base layer polyester preferably comprises at least one aliphatic diol, at least one of which is ethylene glycol. Preferably, the glycol component of the base layer polyester is an aliphatic diol, preferably ethylene glycol.
[0017] Preferred substrate polyesters are selected from polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), or are PET- or PEN-based copolyesters. Particularly preferred is polyethylene terephthalate (PET) or a copolyester thereof. Preferably, the substrate polyester is PET.
[0018] The film-forming polymer resin is the major component of the substrate layer and constitutes at least 70% by weight of the total weight of the substrate layer, preferably at least 80% by weight, preferably at least 85% by weight, preferably at least 90% by weight, preferably at least 95% by weight, more typically at least 98% by weight, more typically at least 99% by weight of the total weight of the substrate layer.
[0019] The intrinsic viscosity of the polyester from which the substrate layer is made is preferably at least about 0.60, preferably at least about 0.61, preferably at least 0.62, preferably at least 0.63, preferably at least 0.64, preferably at least 0.65, preferably at least about 0.70, preferably at least about 0.75. Preferably, the intrinsic viscosity of the substrate layer polyester is 0.85 or less, preferably 0.83 or less.
[0020] Formation of the polyester is conveniently carried out in known manner by condensation or transesterification, generally at temperatures up to about 295° C. In a preferred embodiment, solid state polymerization may be used to increase the intrinsic viscosity of the polyester to a desired value using conventional techniques well known in the art, for example, using a fluidized bed, such as a nitrogen fluidized bed or a vacuum fluidized bed, using a rotary vacuum dryer.
[0021] The substrate layer may further contain additives conventionally used in the manufacture of polyester films. Thus, agents such as particulate fillers, antiblocking agents (or slip additives), antifog agents, hydrolysis stabilizers, antioxidants, UV stabilizers, crosslinking agents, dyes, lubricants, radical scavengers, heat stabilizers, surfactants, gloss enhancers, decomposition accelerators, viscosity modifiers, and dispersion stabilizers may be appropriately incorporated.
[0022] Particularly useful are granular fillers. As is well known in the art, granular fillers can improve handling and winding during production (i.e. function as antiblocking agents) and / or adjust optical properties. They are typically granular inorganic fillers (e.g. metal oxides or semi-metal oxides such as alumina, titania, talc and silica (especially precipitated or diatomaceous silicas and silica gels), calcined china clays and alkali metal salts such as calcium and barium carbonates and sulfates). The granular inorganic fillers are preferably subdivided and their volume distribution median particle size (equivalent spherical diameter corresponding to 50% of the volume of the total particles, read on a cumulative distribution curve relating volume % to particle size, often referred to as the "D(v,0.5)" value) is preferably in the range of 0.01 to 5 μm, more preferably 0.05 to 1.5 μm, particularly preferably 0.15 to 1.2 μm. Preferably, at least 90% by volume, more preferably at least 95% by volume, of the inorganic filler particles are within the range of the volume distribution median particle size ±0.8 μm, in particular ±0.5 μm. The particle size of the filler particles is suitably measured by laser light diffraction.
[0023] Further classes of antiblocking agents, as are conventionally used in the art, are fatty amides (such as erucamide, stearyl erucamide, or benhamide) and waxes (eg, polyolefin waxes, ester waxes, or carnauba wax).
[0024] The conventional additives mentioned above can be introduced into the polymer in a conventional manner, for example by mixing with the monomer reactants from which the film-forming polymer is derived, or the components can be mixed with the polymer by tumbling or dry blending, or by compounding in an extruder, followed by cooling and usually grinding into granules or chips. Masterbatching techniques can also be used.
[0025] The polymeric material of the heat-sealable layer can soften upon heating to a sufficient extent that its viscosity becomes low enough to allow sufficient wetting to adhere to the surface to which it is bonded. The heat-sealable layer is formed from a copolyester blend comprising at least two (preferably only two) copolyesters, referred to herein as copolyester A and copolyester B. It will be understood that each copolyester in the copolyester blend is different from the other copolyester(s) in the copolyester blend, i.e., copolyester A is different from copolyester B.
[0026] The copolyester of the heat-sealable layer may be amorphous or semi-crystalline.
[0027] The glass transition temperature Tg(A) of copolyester A is higher than the glass transition temperature Tg(B) of copolyester B. Preferably, Tg(B) is at least 5° C., preferably 10 to 15° C., lower than Tg(A).
[0028] Preferably, Tg(A) is in the range of -15°C to 5°C, preferably at least -10°C, preferably below 0°C, preferably in the range of -10°C to 0°C.
[0029] Preferably, Tg(B) is in the range of -35°C to -10°C, preferably at least -30°C, preferably below -15°C, preferably in the range of -30°C to -15°C.
[0030] Each of said copolyesters of the heat-sealable layer is derived from at least three different monomer repeat units, and preferably only three different monomer repeat units, where the monomer repeat units are selected from dicarboxylic acid(s) and glycol(s) as described above. A preferred copolyester is derived from an aromatic dicarboxylic acid, an aliphatic dicarboxylic acid and a glycol. The aromatic dicarboxylic acid is preferably terephthalic acid and the aliphatic dicarboxylic acid is preferably a copolymer having the general formula C n H 2n(COOH)2, where n is 2 to 8 (such as succinic acid, glutaric acid, sebacic acid, adipic acid, azelaic acid, suberic acid, or pimelic acid), and the glycol is preferably an aliphatic diol, preferably ethylene glycol.
[0031] The aromatic dicarboxylic acid in each of the copolyesters is preferably the same, i.e., the aromatic dicarboxylic acid in copolyester A is the same as the aromatic dicarboxylic acid in copolyester B. Similarly, the glycol in each of the copolyesters is preferably the same, i.e., the glycol in copolyester A is the same as the glycol in copolyester B. In a preferred embodiment, the copolyesters differ in the identity of the aliphatic dicarboxylic acid, i.e., the aliphatic dicarboxylic acid in copolyester A is different from the aliphatic dicarboxylic acid in copolyester B.
[0032] The molar ratio of aromatic dicarboxylic acid (Ar-diacid) to aliphatic dicarboxylic acid (Al-diacid) in the copolyester (Ar-diacid:Al-diacid) is preferably in the range of 90:10 to 10:90, preferably 80:20 to 20:80, preferably 70:30 to 30:70, preferably 60:40 to 30:70, preferably 60:40 to 40:60. Thus, the aliphatic dicarboxylic acid preferably constitutes 10 to 90 mol %, preferably 20 to 80 mol %, preferably 30 to 70 mol %, preferably 40 to 60 mol % of the total acid fraction of the copolyester, with the remainder being constituted by aromatic dicarboxylic acid.
[0033] Preferably, the aliphatic dicarboxylic acid content of copolyester A is lower than the aliphatic dicarboxylic acid content of copolyester B.
[0034] Therefore, the aliphatic dicarboxylic acid content of the copolyester A is preferably 50 mol % or less, preferably 10 to 50 mol %, preferably 20 to 50 mol %, preferably 30 to 50 mol %, for example 40 to 50 mol %, of the total acid fraction of the copolyester.
[0035] Preferably, the aliphatic dicarboxylic acid content of copolyester B is more than 40 mol%, preferably more than 45 mol%, preferably more than 50 mol%, preferably more than 55 mol%, preferably between 50 and 90 mol%, preferably between 50 and 80 mol%, preferably between 50 and 70 mol%, for example between 50 and 60 mol%, of the total acid fraction of the copolyester.
[0036] The copolyesters may be amorphous or semi-crystalline.
[0037] Copolyester A is the predominant copolyester in the heat-sealable layer and is preferably present in an amount W of at least 50% by weight, preferably from 50 to 90% by weight, preferably from 50 to 89% by weight of the total weight of the heat-sealable polymer layer. A It exists in.
[0038] Copolyester B is the minor copolyester in the heat-sealable layer and is preferably present in an amount W of at least 10% by weight, preferably from 10 to 50% by weight, preferably from 10 to 45% by weight of the total weight of the heat-sealable polymer layer. B It exists in.
[0039] Without wishing to be bound by theory, the inventors believe that the primary function of copolyester A is to control the seal strength of the film to the container to which it is sealed, and the primary function of copolyester B is to control or balance the peel performance of the film from the container.
[0040] Preferably, the heat-sealable layer further comprises one or more antiblocking agent(s) to improve the handling properties of the film. Preferably, the total amount of antiblocking agent(s) is about 5% by weight or less, preferably about 1 to about 5% by weight of the total weight of the heat-sealable polymeric layer. Preferably, the heat-sealable layer comprises multiple antiblocking agents, such as a silica antiblocking agent and an organic antiblocking agent, as described above.
[0041] Preferably, the heat-sealable polymer layer comprises 50-89 wt. % of copolyester A, 10-45 wt. % of copolyester B, and 1-5 wt. % of antiblocking agent(s), based on the total weight of the heat-sealable polymer layer.
[0042] Optionally, the heat-sealable layer may further comprise one or more other additive(s) conventional in polyester films, as described above, in particular the layer may further comprise one or more tackifier(s) and / or one or more anti-fog agent(s). The total amount of any tackifier(s) present in the heat-sealable layer should be about 30% by weight or less based on the total weight of the heat-sealable polymer layer. The total amount of any anti-fog agent(s) present in the heat-sealable layer should be about 10% by weight or less based on the total weight of the heat-sealable polymer layer. The tackifier provides increased adhesion to the heat-sealable layer composition. Suitable tackifiers are well known in the art and include a variety of natural and synthetic resins, typically falling into three categories: hydrocarbon resins (including C5 aliphatic resins, C9 aromatic resins, and DCPD cycloaliphatic resins); rosin esters; and terpene resins (particularly pinene-based polyterpenes and phenol- and styrene-modified pinene-based terpenes). Tackifying resins may be liquid, semi-solid to solid, or solid, and generally comprise complex amorphous materials in the form of mixtures of organic compounds that do not have a distinct melting point and do not tend to crystallize. Such tackifying resins may be insoluble in water, may be of vegetable or animal origin, or may be synthetic. Suitable tackifying agents therefore include, but are not limited to, para-coumarone-indene resins, terpenes (including styrenated terpenes), aromatic hydrocarbon resins, aromatic / aliphatic hydrocarbon resins, and their partially or fully hydrogenated derivatives, rosin and rosin esters. Tackifying agents may also include butadiene-styrene resins and polybutadiene resins. "Anti-fog agents" prevent or delay the formation of water droplets on the surface of the film. Suitable anti-fog agents are well known in the art and may be selected, for example, from surfactants designed to reduce the surface tension of water, such as sorbitan, fatty esters, glycerol monostearate, glycerol monooleate, and fatty alcohols.
[0043] It will be understood that the amounts (wt %) of copolyester A, copolyester B, the preferred antiblocking agent(s), and optional conventional additive(s), such as tackifier(s) and antifog agent(s), should total 100%.
[0044] The softening point of the copolyester A is preferably from 120 to 160°C, preferably from 130 to 150°C, measured according to ASTM E28-18.
[0045] The softening point of the copolyester B is preferably from 60 to 120°C, preferably from 80 to 110°C, measured according to ASTM E28-18.
[0046] Copolyester A preferably has a tensile strength at break of at least 1000 psi, as measured according to ASTM D638-14. (6894.76kPa) , preferably 1500 to 5000 psi (10342.14~34473.8kPa) It is.
[0047] Copolyester B preferably has a tensile strength at break of at least 200 psi, measured according to ASTM D638-14. (1378.95kPa) , preferably 250 to 1500 psi (1723.69~10342.14kPa) , preferably 1500 psi(10342.14kPa) is less than.
[0048] The elongation at break of copolyester A, measured according to ASTM D638-14, is preferably at least 250%, preferably from 500 to 2000%.
[0049] The elongation at break of copolyester B, measured according to ASTM D638-14, is preferably at least 500%, preferably between 1000 and 2500%.
[0050] Formation of the composite film can be accomplished by conventional techniques well known in the art. Conveniently, formation of the substrate is accomplished by extrusion according to the procedure described below.
[0051] Generally speaking, the process involves extruding a layer of molten polyester at a temperature in the range of about 275 to about 300°C, preferably about 290 to 295°C, quenching the extrudate, and orienting the preferably quenched extrudate in at least one direction. The film may be uniaxially oriented, but is preferably biaxially oriented by stretching in two mutually perpendicular directions in the plane of the film to achieve a satisfactory combination of mechanical and physical properties. Orientation can be by any process known in the art for producing oriented films, for example, tubular film process or flat film process. Biaxial orientation is achieved by stretching in two mutually perpendicular directions in the plane of the film to achieve a satisfactory combination of mechanical and physical properties. In the tubular process, simultaneous biaxial orientation can be achieved by extruding a thermoplastic polyester tube, which is subsequently quenched, reheated, and then expanded by internal gas pressure to induce transverse orientation, and drawn at a speed to induce longitudinal orientation. Suitable simultaneous biaxial orientation processes are disclosed in EP2108673A and US2009 / 0117362A1, the disclosures of which are incorporated herein by reference.
[0052] In the preferred flat film process, the film-forming polyester is extruded through a slot die and rapidly quenched onto a chilled casting drum to ensure that the polyester is quenched to the amorphous state. Orientation is then achieved by stretching the quenched extrudate in at least one direction at a temperature above the glass transition temperature of the polyester. Sequential orientation can be achieved by stretching the flat quenched extrudate first in one direction, usually the machine direction, i.e., forward through a film stretcher, and then in the transverse direction. Forward stretching of the extrudate is conveniently accomplished over a set of rotating rolls or between two pairs of nip rolls, and transverse stretching is then accomplished in a stenter apparatus.
[0053] Stretching is generally performed so that the dimensions of the stretched film are 2 to 5 times, more preferably 2.5 to 4.5 times, of their original dimensions in the or each direction of stretching. More preferably, stretching is performed so that the dimensions of the oriented film are 3.0 to 3.3 times their original dimensions in forward stretching and 3.3 to 3.9 times their original dimensions in lateral stretching. If orientation in only one direction is required, larger stretch ratios (e.g., up to about 8 times) can be used. Stretching is conventionally performed at a temperature higher than the Tg of the substrate layer polyester, preferably at least about 5°C higher than Tg, preferably at least about 15°C higher than Tg, preferably in the range of about Tg+5°C to about Tg+75°C, preferably about Tg+5°C to about Tg+30°C. Thus, typically, stretching is performed at a temperature in the range of about 5 to about 155°C, preferably about 5 to about 110°C. It is not necessary to stretch equally in the machine and transverse directions, but this is preferred when balanced properties are desired.
[0054] The stretched film may be, and preferably is, dimensionally stabilized by heat setting under dimensional support at a temperature above the glass transition temperature but below the melting temperature of the substrate layer polyester to induce the desired crystallization of the polymer. During heat setting, a small amount of dimensional relaxation can be performed in the transverse direction (TD) by a procedure known as "toe-in". Toe-in can include dimensional relaxation on the order of 2-4%. Dimensional relaxation in the process or machine direction (MD) is also possible, as is known in the art. The actual heat setting temperature and time will vary depending on the composition of the film and its desired final heat shrinkage, but should not be selected to substantially degrade the toughness properties of the film, such as tear resistance. Within these constraints, preferred films are heat set at a temperature about 80°C below the melting temperature of the substrate layer polyester (i.e., T M -80℃)~T M Approximately 10°C lower than the M −10° C.), preferably at about T M -70℃~approx.T MIt is heat set at a temperature of −20° C. Thus, the heat setting temperature is suitably in the range of from about 130 to about 245° C., preferably from about 150 to about 245° C., preferably at least 180° C., preferably from 190 to 230° C. After heat setting, the film is typically rapidly quenched to induce the desired crystallinity in the polymer.
[0055] The film may be further stabilized through the use of an in-line relaxation step. Alternatively, the relaxation treatment may be performed offline. In this additional step, the film is heated at a temperature lower than that of the heat-setting step, with the tension in MD and TD being significantly reduced. The tension the film is subjected to is a low tension, typically less than 5 kg / m of film width, preferably less than 3.5 kg / m, preferably less than 2.5 kg / m, typically in the range of 1.0-2.0 kg / m. In the case of a film speed controlled relaxation process, the reduction in film speed (and therefore strain relaxation) is typically in the range of 0-2.5%, preferably 0.5-2.0%. The transverse dimensions of the film do not increase during the heat stabilization step. The temperature used for the heat stabilization step may vary depending on the combination of properties desired in the final film, with higher temperatures resulting in better, i.e. lower, residual shrinkage properties. Temperatures of 135-250°C are generally desirable, with 150-230°C being preferred, and 170-200°C being more preferred. The duration of heating depends on the temperature used but typically ranges from 10 to 40 seconds, with a duration of 20 to 30 seconds being preferred. This heat stabilization process can be carried out by a variety of methods, including planar and vertical configurations, and either "off-line" as a separate process step or "in-line" as a continuation of the film manufacturing process. Films treated in this manner exhibit less thermal shrinkage than those produced in the absence of such post-heat-set relaxation.
[0056] The formation of the film comprising the polyester substrate layer and the heat-sealable layer is preferably carried out by coating the heat-sealable layer composition onto the substrate layer. Coating can be carried out using any suitable coating technique, including spray coating, roll coating, slot coating, meniscus coating, dip coating, wire bar coating, air knife coating, curtain coating, doctor knife coating, direct or reverse gravure coating, and the like. Coating can be carried out "off-line", i.e. after any stretching and subsequent heat setting used during the manufacture of the substrate layer, or "in-line", i.e. the coating step is carried out before, during, or between any stretching operation(s) used. In-line coating operations for biaxially oriented films are typically carried out between the forward and lateral stretches of the biaxial stretch ("inter-draw" coating). In the present invention, coating is preferably carried out off-line, i.e. after the manufacture of the substrate layer.
[0057] Preferably, the heat-sealable polymer layer is applied to the substrate by coating a coating composition comprising the components of the heat-sealable layer in a coating vehicle, typically an organic solvent or mixtures thereof, which is conventional in the art and generally referred to as solution coating. Any suitable coating vehicle or solvent conventional in the art can be used, such as THF, ethyl acetate, methyl ethyl ketone, acetone, toluene, dioxolane, cyclohexanone, xylene, butyl acetate, methyl isobutyl ketone or chlorinated solvents, typically THF or toluene. The amount of coating vehicle present in the coating composition typically ranges from 40 to 80% by weight of the coating composition, with the remainder of the coating composition being comprised of the copolyester, the preferred antiblocking agent, and optionally the tackifier, antifog agent, and other conventional additive(s) described herein above. After coating, the coated substrate is dried to remove the coating vehicle and provide a film of the heat-sealable polymer layer on the polyester substrate layer.
[0058] The total thickness of the film is preferably about 5 to about 250 μm, preferably about 8 to about 125 μm, preferably about 8 to about 50 μm, preferably about 12 to about 26 μm.
[0059] The thickness of the heat-sealable layer is preferably 30% or less, more preferably 25% or less, more preferably 20% or less, preferably at least 2.5%, more preferably at least 5%, preferably about 10% to about 20% of the total thickness of the polymer film. Typically, the thickness of the heat-sealable layer is about 25 μm or less, preferably about 10 μm or less, more preferably about 5 μm or less, preferably about 2 μm or less, preferably at least 0.5 μm, preferably in the range of about 0.5 to about 5 μm. Preferably, the coat weight of the heat-sealable polymer layer is about 1 to about 5 g / m. 2 It is.
[0060] The heat seal peel strength of the film is preferably from 500 to 1400 g / in when measured as defined herein, i.e., heat sealed at a temperature in the range of 121 to 204° C., a dwell time of 1 second, and a pressure of 40 psi (275.79 kPa). (500~1400g / 25.4mm) , preferably 500 to 1200 g / inch (500~1200g / 25.4mm) Preferably, the heat seal peel strength of the film is in the range of 500 to 1400 g / in when heat sealed as described herein at any temperature in the range of 121 to 204° C., with a 1 second dwell time and a pressure of 40 psi (275.79 kPa). (500~1400g / 25.4mm) , preferably 500 to 1200 g / inch (500~1200g / 25.4mm) Such heat seal peel strength provides a sufficiently strong seal without risk of leakage and reduces the risk of shredding the cap liner during peeling.
[0061] The films of the first aspect of the invention are particularly useful as sealant films, including lidding films and cap liner films, to seal containers in many applications, such as containers that serve as containers for products such as food, drugs, beverages, chemicals such as alkalis, acids, oils, organic solvents, flammable materials, powders, pellets, and the like.
[0062] The films, lidding films and cap liners of the present invention are particularly useful for creating a hermetic seal.
[0063] The containers can be made from a variety of materials, particularly plastics (especially polyester) or glass. The containers can be made from polyester materials, particularly useful are APET / CPET trays (where APET refers to amorphous PET and CPET refers to crystalline (or semi-crystalline) PET).
[0064] The lidding film may optionally include a metal foil layer disposed on the film of the first embodiment, resulting in a layer sequence of metal foil layer / polyester substrate layer / heat sealable polymer layer.
[0065] The film of the first aspect of the present invention may also function as a lidding film without the metal foil layer, such a lidding film being particularly useful as a sealant film for APET / CPET trays.
[0066] According to a second aspect of the present invention there is provided a lidding film comprising the film of the first aspect of the present invention and further comprising a metal foil layer, the layer sequence being metal foil layer / polyester substrate layer / heat sealable polymer layer.
[0067] The metal foil layer may be any suitable metal foil layer used in the art, preferably an aluminum foil layer, and may be of any suitable thickness conventional in the art, preferably in the range of about 25 to about 50 μm.
[0068] Preferably said lidding film is a cap liner.
[0069] The cap liner may be a one-piece cap liner further comprising a paper or foam layer disposed on the side of the metal foil layer remote from the polymeric substrate layer, in which case the layer sequence is paper or foam layer / metal foil layer / polyester substrate layer / heat sealable layer. An adhesive layer is preferably disposed between the metal foil layer and the paper or foam layer, as is conventional in the cap liner art, and any suitable adhesive may be used.
[0070] The cap liner may be a two-piece cap liner including, in order, a pulp board layer, a wax layer, a metal foil layer, a polymeric substrate layer, and a heat-sealable polymer layer.
[0071] The paper, foam, pulpboard and wax layers may be any conventional paper, foam, pulpboard and wax layers known and used in the art of cap liners. The thickness of the paper, foam or pulpboard layer is typically 50 to 1000 μm.
[0072] The cap liner of the second aspect of the invention is preferably manufactured by first producing a film comprising a polymeric substrate layer and a heat-sealable polymer layer, as described above in the first aspect, and then laminating said film with a metal foil layer and said other layers to provide the cap liner.
[0073] The longest dimension of the cap liner is preferably 70mm or less, preferably about 65mm or less. Preferably, the cap liner is circular and has a diameter preferably of 70mm or less, typically about 65mm or less.
[0074] The priorities and disclosures of the first aspect are equally applicable to the second aspect.
[0075] According to a third aspect of the present invention there is provided a method of sealing a container including an opening, said method comprising the steps of: (i) providing or preparing a film according to the first aspect of the present invention; (ii) laminating the film from step (i) with a metal foil and either a paper or foam layer or a pulp board layer and a wax layer to form a cap liner according to the second aspect of the invention; (iii) providing a container; (iv) providing a cap to the container; (v) inserting the cap liner from step (ii) inside the cap; (vi) placing a cap over the opening of the container such that the heat-sealable layer of the cap liner contacts the container; and (vii) typically including subjecting the cap to electromagnetic induction heating by passing the cap and container assembly under an induction coil, thereby sealing the cap liner to the container.
[0076] The cap may be, for example, any cap or other closure device as known and used in the art. The cap is typically made from a polymeric material, such as polypropylene or polyethylene. It will be appreciated that a suitable cap has a flat top and a sidewall extending substantially perpendicularly from the flat top. The inner surface of the sidewall may exhibit a screw thread disposed therein. The cap is preferably substantially cylindrical and closed at one end by the flat top.
[0077] The container may be any conventional container known and used in the art, for example, such containers are typically plastic (especially polyester) or glass containers. The opening of the container typically exhibits a circular cross section. The container preferably comprises a body portion and a cylindrical neck portion, preferably the neck portion exhibits a screw thread.
[0078] The cap liner is inserted into the cap so that the paper or foam or pulp board layer contacts the inside surface of the flat top of the cap and so that the heat-sealable layer is exposed and available to contact the container being sealed.
[0079] It will be appreciated that the method of the third aspect preferably further comprises the step of cutting said film or said cap liner to an appropriate size so that it can be inserted inside the cap and juxtaposed with the flat top thereof.
[0080] It will be appreciated that prior to placing a cap over the container opening, the method suitably includes the step of filling the container with a product, such as a food, drug, beverage, alkali, acid, oil, organic solvent, flammable material, powder, pellets, etc.
[0081] It will further be appreciated that during the induction heating step, the cap is in relatively closer proximity to the induction coil than the container is to the induction coil.
[0082] The priorities and disclosures of the first and second aspects are equally applicable to the third aspect.
[0083] According to a fourth aspect of the present invention there is provided a method of sealing a container including an opening, said method comprising the steps of: (i) providing or preparing a film according to the first aspect of the present invention; (ii) laminating the film from step (i) with a metal foil to provide a lidding film according to the second aspect of the invention; (iii) providing a container; (iv) placing the lidding film from step (ii) over the opening of the container such that the heat-sealable layer of the lidding film contacts the container; and (v) subjecting the lidding film to electromagnetic induction heating, typically by passing the lidding film and container assembly under an induction coil, thereby sealing the lidding film to the container.
[0084] In the fourth embodiment of the present invention, there is no additional cap or closure device that overlaps the lid film. The lid film is placed on the container without a cap and induction sealed to the container. Therefore, the method of the fourth embodiment is a capless induction sealing method, also known in the art as "direct application".
[0085] It will be appreciated that the method of the fourth aspect suitably further comprises the step of cutting the lidding film to a suitable size so as to cover the opening of the container and seal to the edge of said opening.
[0086] The priorities and disclosures of the first, second and third aspects are equally applicable to the fourth aspect.
[0087] According to a fifth aspect of the present invention there is provided a method of sealing a container including an opening, said method comprising the steps of: (i) providing or preparing a film according to the first aspect of the present invention; (ii) providing a container; (iii) placing the film from step (i) over the opening of a container such that the heat-sealable layer of the film contacts the container; and (iv) exposing the film to heat and optionally pressure, thereby sealing the film in the container.
[0088] In a fifth embodiment of the invention, there is no additional cap or closure device overlying the film, there is no metal foil layer within the film, and the heat seal bond between the film and the container is achieved by conventional conductive heating, i.e., not by induction heating.
[0089] It will be appreciated that the method of the fifth aspect suitably further comprises the step of cutting the film to a suitable size so as to cover the opening of the container and seal to the edge of said opening.
[0090] The priorities and disclosures of the first aspect are equally applicable to the fifth aspect.
[0091] According to a sixth aspect of the present invention there is provided a sealed container comprising a container having an opening and further comprising a film according to the first aspect of the present invention or a lidding film (preferably a cap liner) according to the second aspect of the present invention sealed around an edge of said opening, preferably said sealed container further comprising a cap positioned over said sealed opening.
[0092] Preferably the sealed container of the sixth aspect is an induction sealed container which may be produced according to the third, fourth or fifth aspects of the invention.
[0093] The priorities and disclosures of the first, second, third, fourth and fifth aspects are equally applicable to the sixth aspect.
[0094] Characteristic measurements The following test methods can be used to characterize the polymer films.
[0095] (i) The intrinsic viscosity of the polyester (in dL / g) is measured in accordance with ASTM D5225-98 (2003) using a Viscotek™ Y-501C relative viscometer (see, e.g., “The dual-capillary method for modern-day viscometry”, Hitchcock, Hammons & Yau, American Laboratory, August 1994) at 25° C. using a 0.5 weight percent solution of the polyester in o-chlorophenol, and the intrinsic viscosity is calculated using the Billmeyer single point method. η=0.25ηred+0.75(ln ηrel) / c During the ceremony, η=intrinsic viscosity (dL / g), ηrel = relative viscosity, c = concentration (g / dL), and ηred=reduced viscosity (dL / g), which is equal to (ηrel-1) / c (also expressed as ηsp / c, where ηsp is the specific viscosity).
[0096] (ii) Glass transition temperature (T g ) and crystalline melting point (T m ) was measured by differential scanning calorimetry (DSC) using a PerkinElmer HyperDSC 8500. Unless otherwise stated, measurements were performed according to the following standard test method, as described in ASTM E1356-98. Samples were kept under a dry nitrogen atmosphere for the duration of the scan. Flow rate 20 ml min -1 and an Al pan were used. The sample (5 mg) was heated from 20°C to 350°C at 20°C / min.
[0097] As stated in ASTM E1356-98, T g The value of T was determined as the extrapolated onset temperature of the glass transition observed in the DSC scan (heat flow (W / g) versus temperature (°C)). m The value of was determined from the DSC scan as the peak endotherm of the transition.
[0098] (iii) Softening point was measured as ring and ball softening point in accordance with ASTM E28-18.
[0099] (iv) The tensile strength and elongation at break of the copolyesters were measured according to ASTM D638-14 using a Type I sample configuration.
[0100] (v) The crystallinity was calculated from the above DSC analysis according to the following equation (X c ) was measured. X c = ΔH m / ΔH m ° During the ceremony, ΔH m = experimental enthalpy of fusion calculated from the integration of the melting endotherm; ΔH m ° = theoretical enthalpy of fusion of the corresponding poly(alkylene-carboxylate) homopolymer at 100% crystallinity. Thus, for PET (or PET-based) polyesters, as defined in the literature, ΔH m ° is the theoretical enthalpy of fusion of 100% crystalline PET polymer (140 J / g), and for PEN (or PEN-based) polyester, ΔH m ° is the theoretical enthalpy of fusion of 100% crystalline PEN polymer (103 J / g) (B. Wunderlich, Macromolecular Physics, Academic Press, New York, (1976)).
[0101] (vi) The heat seal peel strength of the films was evaluated by measuring the seal strength of the coated films to the APET layer of the APET-CPET coextruded substrate (APET: amorphous PET; CPET: crystalline PET; total thickness of the substrate was 330 μm). The coated films were heat sealed to the APET-coex-CPET substrate at three different temperatures using a Sentinel heat sealer (Model 12, Packaging Industries Group Inc.). The heat sealer temperatures (upper jaw) were 121°C (T1), 177°C (T2), and 204°C (T3), with a dwell time of 1 second and a pressure of 40 psi (275.79 kPa). The lower jaw was approximately 38°C when the upper jaw temperature was varied. The sealed samples were marked and cut into 25 mm wide strips, and the heat seal strength was measured with a Thwing-Albert peel tester. The jaws were set 50 mm apart. The upper jaw held the film strip of the sealed sample and moved up at a speed of 250 mm / min, while the lower jaw held the APET-coex-APET strip of the sealed sample and remained stationary. Six sealed sample strips were measured for each coated sample, and the average force (g / in) required to separate the two film strips was (g / 25.4mm) The lowest force was recorded for sealed samples that shredded. It will be appreciated that for samples that showed shredding, the peel strength varies across the seal area such that the peel strength is greater than the cohesive strength in some areas of the film.
[0102] (vii) Induction seal peel strength of cap liners incorporating the films of the present invention was evaluated by measuring the seal strength of the cap liners to white PET bottles (Packaging Options Direct, US) with a neck diameter of 38 mm and a wall thickness of the bottle neck of 2.2 mm. Seal strength was tested using a Thwing-Albert peel tester according to the test method described above, except that a fixed lower jaw held the PET bottle and an upper jaw peeled the cap liner from the bottle. The cap liner was inserted into a white 38 / 400 cap (SKS Bottle & Pkg, Inc.) and induction sealed to the top of the bottle. The induction seal was performed at 20 lbf*in (pound force-inch) on an Ifoiler Induction Sealer (Pillar Tech. LLC). (2.26Nm) The experiments were performed using a cap torque of 1000 psi, an air gap (from induction sealer head to bottle cap) of 1 / 8 in. (3.175 mm), and a conveyor line speed of 60 ft / min (18.288 m / min). The power of the induction seal system was varied to study the performance of the film at different induction seal settings.
[0103] The testing of the following examples involved the preparation of a one-piece cap liner by laminating a film to an aluminum foil layer (25.4 μm thick) followed by lamination to a paper layer (127 μm thick).
[0104] The present invention will be further described in the following examples. It will be understood that these examples are merely for illustrative purposes and are not intended to limit the invention as described above. Modifications of detail may be made without departing from the scope of the present invention. EXAMPLES
[0105] A series of coating films were prepared by coating the coating composition onto a 12.5 μm thick biaxially oriented PET film and then drying. The dry coat weight of the coating composition was 2.3 g / m 2 The coating composition was as follows:
[0106] Comparative Example 1 A coating solution was prepared by dissolving copolyester 1 (532 g) and copolyester 2 (133 g) in THF (2,800 g) at 55° C., followed by the addition of slip / antiblocking components (fatty amide, 10.5 g; silica, 24.5 g). Copolyester 1 contained azelaic acid with a dicarboxylic acid fraction of 45 mole % and had a viscosity of 2700 psi, measured as defined herein. (18615.85kPa) Copolyester 2 was a PET-based copolyester having a dicarboxylic acid fraction of 33 mole % isophthalic acid and a tensile strength of 11,000 psi and an elongation of 1000%, as measured as defined herein. (75842.36kPa) The result was a PET-based copolyester exhibiting a tensile strength of 1.0 and an elongation of 5%.
[0107] Example 1 A coating solution was prepared by dissolving copolyester 1 (476 g) and copolyester 2 (203 g) in THF (2,800 g) at 55° C., followed by the addition of slip / antiblocking components (fatty amide, 10.5 g; silica, 10.5 g). Copolyester 1 contained azelaic acid with a dicarboxylic acid fraction of 45 mole % and had a viscosity of 2700 psi, measured as defined herein. (18615.85kPa) Copolyester 2 was a PET-based copolyester having a dicarboxylic acid fraction of 58 mole % sebacic acid and a tensile strength of 1000 psi and an elongation of 1000%, measured as defined herein. (6894.76kPa) The PET-based copolyester exhibited a tensile strength of 1000 and an elongation of 1600%.
[0108] Example 2 A coating solution was prepared by dissolving copolyester 1 (476 g) and copolyester 2 (203 g) in THF (2,800 g) at 55° C., followed by the addition of slip / antiblocking components (fatty amide, 10.5 g; silica, 10.5 g). Copolyester 1 contained azelaic acid with a dicarboxylic acid fraction of 45 mole % and was heated to 2500 psi, as measured herein. (17236.9kPa) Copolyester 2 was a PET-based copolyester having a dicarboxylic acid fraction of 58 mole % sebacic acid and a tensile strength of 1000 psi and an elongation of 1200%, as measured as defined herein. (6894.76kPa) The PET-based copolyester exhibited a tensile strength of 1000 and an elongation of 1600%.
[0109] Cap Liner Each film was made into a one-piece cap liner by laminating the film to an aluminum foil layer (25.4 μm thick) followed by a foam paper layer (127 μm thick). The cap liner was inserted into a white 38 / 400 cap (SKS Bottle & Pkg, Inc.) and induction sealed to a white PET bottle (Packaging Options Direct, US) with a neck diameter of 38 mm and a bottle neck wall thickness of 2.2 mm. The induction seal was performed on an Ifoiler Induction Sealer (Pillar Tech. LLC) at 20 lbf*in (pound force-inch). (2.26Nm) The test was performed using a cap torque of 1000 psi, an air gap (from induction sealer head to bottle cap) of 1 / 8 inch (3.175 mm), and a conveyor line speed of 60 ft / min (18.288 m / min).
[0110] Table 1 shows the properties of the copolyesters, films containing them, and cap liners made therefrom, characterized according to the test methods described above.
[0111] The data in Table 1 show that the variation in heat seal peel strength over the temperature range of 121-204°C is much greater for Comparative Example 1 and advantageously smaller for Examples 1 and 2. Thus, the examples of the present invention advantageously show much smaller variations in heat seal strength with changes in temperature. It will be appreciated that temperature can be more precisely controlled in a heat seal system than in an induction system, and heat seal tests were conducted at different temperatures to replicate the various temperature conditions in a conventional induction seal system.
[0112] The data in Table 1 also show that the variation in heat seal peel strength after aging is much greater for Comparative Example 1 and advantageously smaller for Examples 1 and 2. Thus, the inventive examples advantageously show much smaller increases in heat seal strength over time.
[0113] A similar trend was observed for the induction seal peel strength data in Table 1. Variation in peel strength after aging was advantageously much smaller for Example 2 (Example 1 was not tested) compared to Comparative Example 1, which was observed at all power settings tested for each film. The power settings were adjusted to optimize the seal strength of the heat seal bond. For Comparative Example 1, the optimal setting was 48% of the potential power of the induction seal system, while for Example 2, the optimal setting was 32% of the potential power of the induction seal system to provide a post-aging peel strength comparable to Comparative Example 1. It will be appreciated that the examples of the present invention also surprisingly allow for a reduction in the energy used to create a suitable heat seal bond, thereby improving the economics and sustainability of the process. [Table 1] The present disclosure includes the following embodiments. <Embodiment 1> A polymeric film comprising a polyester substrate layer and a heat-sealable polymer layer disposed on one surface of the polyester substrate layer, the heat-sealable polymer layer being made of a material selected from the group consisting of W A A copolyester A having a glass transition temperature Tg(A) in an amount of W B and a copolyester B having a glass transition temperature Tg(B) in an amount of (i) W A >W B , (ii) W A is at least 50% by weight of the total weight of the heat-sealable polymer layer; (iii) W B is at least 10% by weight of the total weight of the heat-sealable polymer layer; (iv) Tg(A)>Tg(B); (v) Tg(B) is in the range of -35°C to -10°C, and (vi) The polymer film, wherein Tg(A) is preferably in the range of -15°C to 5°C. <Embodiment 2> 2. The polymeric film of embodiment 1, wherein the polyester substrate layer is oriented, preferably biaxially oriented. <Embodiment 3> 3. The polymeric film of embodiment 1 or 2, wherein the substrate layer polyester is polyethylene terephthalate (PET) or a PET-based copolyester. <Embodiment 4> 4. The polymer film according to any one of the preceding embodiments, wherein the Tg(B) is at least 5° C., preferably 10-15° C., lower than the Tg(A). <Embodiment 5> 5. The polymer film according to any one of embodiments 1 to 4, wherein the Tg(A) is in the range of -10°C to 0°C. <Embodiment 6> 6. The polymer film according to any one of embodiments 1 to 5, wherein the Tg(B) is in the range of -30°C to -15°C. <Embodiment 7> The copolyester A and the copolyester B are independently selected from copolyesters derived from at least three different monomer repeat units, preferably three different monomer repeat units, preferably derived from an aromatic dicarboxylic acid, an aliphatic dicarboxylic acid and a glycol, preferably the aromatic dicarboxylic acid is terephthalic acid and preferably the aliphatic dicarboxylic acid is represented by the general formula C n H 2n 7. The polymer film of any one of the preceding embodiments, having a formula (COOH)2, where n is 2 to 8, preferably the glycol is ethylene glycol. <Embodiment 8> 8. The polymer film of any one of the preceding claims, wherein the aromatic dicarboxylic acid in copolyester A is the same as the aromatic dicarboxylic acid in copolyester B, preferably the glycol in copolyester A is the same as the glycol in copolyester B, and preferably the aliphatic dicarboxylic acid in copolyester A is different from the aliphatic dicarboxylic acid in copolyester B. <Embodiment 9> 9. The polymer film according to any one of the first to eighth embodiments, wherein the copolyester A and the copolyester B are independently selected from copolyesters having an acid fraction containing an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid, the aliphatic dicarboxylic acid comprising 10 to 90 mol %, preferably 20 to 80 mol %, preferably 30 to 70 mol %, preferably 40 to 60 mol % of the total acid fraction of the copolyester, and the remainder comprising the aromatic dicarboxylic acid. <Embodiment 10> 10. The polymer film of any one of the preceding embodiments, wherein the copolyester A has an aliphatic dicarboxylic acid content lower than the aliphatic dicarboxylic acid content of the copolyester B. <Embodiment 11> 11. The polymer film according to any one of the preceding embodiments, wherein the aliphatic dicarboxylic acid content of the copolyester A is 50 mol % or less, preferably 10 to 50 mol %, preferably 20 to 50 mol %, preferably 30 to 50 mol %, for example 40 to 50 mol %, of the total acid fraction of the copolyester. <Embodiment 12> 12. The polymer film according to any one of the preceding embodiments, wherein the aliphatic dicarboxylic acid content of the copolyester B is more than 40 mol%, preferably more than 45 mol%, preferably more than 50 mol%, preferably more than 55 mol%, preferably from 50 to 90 mol%, preferably from 50 to 80 mol%, preferably from 50 to 70 mol%, for example from 50 to 60 mol%, of the total acid fraction of the copolyester. <Embodiment 13> The copolyester A is the predominant copolyester in the heat-sealable layer and is present in an amount W of 50 to 90% by weight, preferably 50 to 89% by weight, of the total weight of the heat-sealable polymer layer. A 13. The polymer film of any one of the preceding embodiments, wherein the polymer film is present in a range of from 1 to 12. <Embodiment 14> The copolyester B is the lesser copolyester in the heat-sealable layer and is in an amount W of 10 to 50% by weight, preferably 10 to 45% by weight, of the total weight of the heat-sealable polymer layer. B 14. The polymer film of any one of the preceding embodiments, wherein the polymer film is present in a range of from 1 to 13. <Embodiment 15> 15. The polymeric film according to any one of the preceding claims, wherein the heat-sealable layer further comprises one or more anti-blocking agent(s) to improve handling properties of the film, preferably the total amount of the anti-blocking agent(s) is about 5 wt% or less, preferably about 1 to about 5 wt% of the total weight of the heat-sealable polymeric layer, preferably the anti-blocking agent is selected from silica, fatty amides, and waxes, and combinations thereof. <Embodiment 16> 16. The polymer film according to any one of the preceding embodiments, wherein the copolyester A has a softening point of 120 to 160° C., preferably 130 to 150° C., as measured according to ASTM E28-18. <Embodiment 17> 17. The polymer film according to any one of the preceding embodiments, wherein the copolyester B has a softening point of 60 to 120° C., preferably 80 to 110° C., as measured according to ASTM E28-18. <Embodiment 18> 18. The polymeric film of any one of the preceding embodiments, wherein the copolyester A has a tensile strength at break of at least 1000 psi, preferably from 1500 to 5000 psi, as measured according to ASTM D638-14. <Embodiment 19> 19. The polymeric film according to any one of the preceding embodiments, wherein the copolyester B has a tensile strength at break of at least 200 psi, preferably from 250 to 1500 psi, preferably less than 1500, as measured according to ASTM D638-14. <Embodiment 20> 20. The polymer film of any one of the preceding embodiments, wherein the copolyester A has an elongation at break of at least 250%, preferably from 500 to 2000%, as measured according to ASTM D638-14. <Embodiment 21> 21. The polymer film according to any one of the preceding embodiments, wherein the copolyester B has an elongation at break of at least 500%, preferably from 1000 to 2500%, measured according to ASTM D638-14. <Embodiment 22> The heat-sealable polymer layer preferably has a thickness of 1 to 5 g / m 2 22. The polymeric film of any one of the preceding claims, wherein the coated heat-sealable polymer layer has a dry coat weight of <Embodiment 23> 23. The polymer film according to any one of the preceding embodiments, wherein the total thickness of the film is from 5 to 250 μm, preferably from 8 to 125 μm, preferably from 8 to 50 μm, preferably from 12 to 26 μm. <Embodiment 24> 24. The polymeric film of any one of the preceding embodiments, wherein the heat seal peel strength of the film is in the range of 500-1400 g / in, preferably 500-1200 g / in, when heat sealed to the APET layer of an APET-CPET coextruded substrate at a 1 second dwell time, a pressure of 40 psi (275.79 kPa), and a temperature in the range of 121-204° C. (preferably any temperature), measured as defined herein. <Embodiment 25> A lidding film comprising the film of any one of embodiments 1-24, further comprising a metal foil layer, the layer sequence being metal foil layer / polyester substrate layer / heat sealable polymer layer. <Embodiment 26> 26. The lidding film of embodiment 25, wherein the metal foil layer is an aluminum foil layer and / or the thickness of the metal foil layer is in the range of about 25 to about 50 μm. <Embodiment 27> 27. A lidding film according to embodiment 25 or 26, wherein the longest dimension of the lidding film is 70mm or less, preferably the lidding film is circular, preferably having a diameter of 70mm or less. <Embodiment 28> 28. The lidding film of any of claims 25-27, further comprising a paper or foam layer disposed on a side of the metal foil layer remote from the polymeric substrate layer, wherein the layer sequence is paper or foam layer / metal foil layer / polyester substrate layer / heat sealable layer, and preferably an adhesive layer is disposed between the metal foil layer and the paper or foam layer. <Embodiment 29> 28. The lidding film of any of embodiments 25-27, further comprising a pulp board layer and a wax layer, such that the layer sequence is pulp board layer / wax layer / metal foil layer / polymeric substrate layer / heat sealable polymer layer. <Embodiment 30> 30. The lidding film of embodiment 28 or 29, wherein the paper, foam, or pulp board layer has a thickness of 50-1000 μm. <Embodiment 31> 31. The lidding film of any one of embodiments 25 to 30, which is a cap liner. <Embodiment 32> 1. A method of sealing a container including an opening, the method comprising: (i) providing or preparing a film according to any one of embodiments 1 to 24; (ii) laminating the film from step (i) with a metal foil, and either a paper or foam layer or a pulp board layer and a wax layer to form a cap liner according to any one of embodiments 25-31; (iii) providing a container; (iv) providing a cap for said container; (v) inserting the cap liner from step (ii) inside the cap; (vi) placing the cap over the opening of the container such that the heat-sealable layer of the cap liner contacts the container; (vii) subjecting the cap to electromagnetic induction heating, thereby sealing the cap liner to the container. <Embodiment 33> 1. A method of sealing a container including an opening, the method comprising: (i) providing or preparing a film according to any one of embodiments 1 to 24; (ii) laminating the film from step (i) with a metal foil to provide a lidding film according to any one of embodiments 25-27; (iii) providing a container; (iv) placing the lidding film from step (ii) over the opening of the container such that the heat-sealable layer of the lidding film contacts the container; (v) subjecting the lidding film to electromagnetic induction heating, thereby sealing the lidding film to the container. <Embodiment 34> 1. A method of sealing a container including an opening, the method comprising: (i) providing or preparing a film according to any one of embodiments 1 to 24; (ii) providing a container; (iii) placing the film of step (i) over the opening of the container such that the heat-sealable layer of the film contacts the container; (iv) exposing the film to conductive heat and optionally pressure, thereby sealing the film to the container. <Embodiment 35> A sealed container comprising a container having an opening and further comprising the film of any of embodiments 1-24 or the lidding film (preferably a cap liner) of any of embodiments 25-31, wherein the film, lidding film or cap liner is sealed around the edge of the opening, preferably the sealed container further comprises a cap placed over the sealed opening, preferably the sealed container is an induction sealed container.
Claims
1. A polymeric film comprising a polyester substrate layer and a heat-sealable polymer layer disposed on one surface of the polyester substrate layer, the heat-sealable polymer layer being made of a material selected from the group consisting of W A and W B and a copolyester B having a glass transition temperature Tg(B) in an amount of (i)W A >W B 、 (ii) W A is at least 50% by weight of the total weight of the heat-sealable polymer layer; (iii) W B is at least 10% by weight of the total weight of the heat-sealable polymer layer; (iv) Tg(A)>Tg(B), (v) Tg(B) is in the range of −35° C. to −10° C.; and (vi) The polymer film has a Tg(A) in the range of -15°C to 5°C.
2. The polymeric film of claim 1 , wherein the polyester substrate layer is oriented.
3. 10. The polymeric film of claim 1, wherein the substrate layer polyester is polyethylene terephthalate (PET) or a PET-based copolyester.
4. 2. The polymer film of claim 1, wherein the Tg(B) is at least 5° C. lower than the Tg(A).
5. 2. The polymer film of claim 1, wherein the Tg(A) is in the range of -10°C to 0°C.
6. 2. The polymer film of claim 1, wherein the Tg(B) is in the range of -30°C to -15°C.
7. 2. The polymeric film of claim 1, wherein said copolyester A and said copolyester B are independently selected from copolyesters derived from aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and glycols.
8. The polymer film of claim 7, wherein the aromatic dicarboxylic acid is terephthalic acid, the aliphatic dicarboxylic acid has the general formula C n H 2n (COOH) 2 (wherein n is 2 to 8), and the glycol is ethylene glycol.
9. 8. The polymeric film of claim 7, wherein the aromatic dicarboxylic acid in said copolyester A is the same as the aromatic dicarboxylic acid in said copolyester B.
10. 2. The polymer film of claim 1, wherein said copolyester A and said copolyester B are independently selected from copolyesters whose acid fraction contains an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid, said aliphatic dicarboxylic acid comprising 10-90 mol % of the total acid fraction of said copolyester, with the remainder being comprised of said aromatic dicarboxylic acid.
11. 8. The polymeric film of claim 7, wherein the aliphatic dicarboxylic acid content of said copolyester A is lower than the aliphatic dicarboxylic acid content of said copolyester B.
12. 8. The polymer film of claim 7, wherein the aliphatic dicarboxylic acid content of said copolyester A is less than or equal to 50 mol % of the total acid fraction of said copolyester.
13. 8. The polymeric film of claim 7, wherein the aliphatic dicarboxylic acid content of said copolyester B is greater than 40 mol % of the total acid fraction of said copolyester.
14. The copolyester A is the predominant copolyester in the heat-sealable layer and is present in an amount W of 50 to 90% by weight of the total weight of the heat-sealable polymer layer. A The polymeric film of claim 1 , wherein
15. The copolyester B is the minor copolyester in the heat-sealable layer and is in an amount W of 10 to 50% by weight of the total weight of the heat-sealable polymer layer. B The polymeric film of claim 1 , wherein
16. 10. The polymeric film of claim 1, wherein the heat-sealable layer further comprises one or more anti-blocking agent(s) to improve handling properties of the film.
17. 2. The polymeric film of claim 1, wherein the copolyester A has a softening point of 120 to 160° C. as measured according to ASTM E28-18.
18. 2. The polymeric film of claim 1, wherein the softening point of said copolyester B is from 60 to 120° C. as measured according to ASTM E28-18.
19. 2. The polymeric film of claim 1, wherein said copolyester A has a tensile strength at break of at least 1000 psi (6894.76 kPa) as measured according to ASTM D638-14.
20. 2. The polymeric film of claim 1, wherein said copolyester B has a tensile strength at break of at least 200 psi (1378.95 kPa) as measured according to ASTM D638-14.
21. 2. The polymeric film of claim 1, wherein said copolyester A has an elongation at break of at least 250% as measured according to ASTM D638-14.
22. 2. The polymeric film of claim 1, wherein said copolyester B has an elongation at break of at least 500%, as measured according to ASTM D638-14.
23. The polymeric film of claim 1 , wherein the heat-sealable polymeric layer is a coated heat-sealable polymeric layer.
24. The polymer film of claim 1, wherein the total thickness of the film is from 5 to 250 μm.
25. 10. The polymeric film of claim 1, wherein the heat seal peel strength of the film is in the range of 500-1400 g / inch (500-1400 g / 25.4 mm) when heat sealed to the APET layer of an APET-CPET coextruded substrate at a 1 second dwell time, a pressure of 40 psi (275.79 kPa), and a temperature in the range of 121-204° C., measured as defined herein.
26. A lidding film comprising the film of any of claims 1 to 25, further comprising a metal foil layer, the layer sequence being metal foil layer / polyester substrate layer / heat sealable polymer layer.
27. 27. The lidding film of claim 26, wherein the metal foil layer is an aluminium foil layer and / or the thickness of the metal foil layer is in the range of 25 to 50 μm.
28. 27. A lidding film according to claim 26, wherein the longest dimension of the lidding film is 70mm or less.
29. 27. The lidding film of claim 26, further comprising a paper or foam layer disposed on a side of the metal foil layer remote from the polymeric substrate layer, the layer sequence being paper or foam layer / metal foil layer / polyester substrate layer / heat sealable layer.
30. 27. The lidding film of claim 26 further comprising a pulpboard layer and a wax layer such that the layer sequence is pulpboard layer / wax layer / metal foil layer / polymeric substrate layer / heat sealable polymer layer.
31. A lidding film according to claim 30, wherein the pulp board layer has a thickness of from 50 to 1000 μm.
32. 27. The lidding film of claim 26 which is a cap liner.
33. 1. A method of sealing a container including an opening, the method comprising: (i) providing or preparing a film according to any one of claims 1 to 25; (ii) laminating the film from step (i) with a metal foil, and either a paper or foam layer or a pulp board layer and a wax layer to form the cap liner of claim 32 having a layer sequence of (a) paper or foam layer / metal foil layer / polyester substrate layer / heat sealable polymer layer or (b) pulp board layer / wax layer / metal foil layer / polymer substrate layer / heat sealable polymer layer; (iii) providing a container; (iv) providing a cap for said container; (v) inserting the cap liner from step (ii) inside the cap; (vi) placing the cap over the opening of the container such that the heat-sealable layer of the cap liner contacts the container; (vii) subjecting the cap to electromagnetic induction heating, thereby sealing the cap liner to the container.
34. 1. A method of sealing a container including an opening, the method comprising: (i) providing or preparing a film according to any one of claims 1 to 25; (ii) laminating the film from step (i) with a metal foil to provide the lidding film of claim 26; (iii) providing a container; (iv) placing the lidding film from step (ii) over the opening of the container such that the heat-sealable layer of the lidding film contacts the container; (v) subjecting the lidding film to electromagnetic induction heating, thereby sealing the lidding film to the container.
35. 1. A method of sealing a container including an opening, the method comprising: (i) providing or preparing a film according to any one of claims 1 to 25; (ii) providing a container; (iii) placing the film of step (i) over the opening of the container such that the heat-sealable layer of the film contacts the container; (iv) exposing the film to conductive heat and optionally pressure, thereby sealing the film to the container.
36. A sealed container comprising a container having an opening, further comprising the film of any of claims 1-25, wherein the film is sealed around an edge of the opening.
37. 27. A sealed container comprising a container having an opening, further comprising the lidding film of claim 26, wherein the lidding film is sealed around an edge of the opening.
38. A sealed container as described in claim 36 or claim 37, further comprising a cap positioned over the sealed opening.
39. The sealed container described in claim 36 or claim 37, wherein the sealed container is an induction sealed container.
Citation Information
Patent Citations
A polyester film that can be heat-sealed at low temperatures and a method for manufacturing the same.
JP2004530000A
Breathable heat-sealable composite polymer film
JP2008526570A
Laminated body and packaging bag
JP2009233969A
Press-through-pack packaging body lid material and press-through-pack packaging body
JP2018188181A
Packaging laminate film and package
JP2019156441A